2020
DOI: 10.1051/e3sconf/202015804006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals in RDF for thermochemical conversion

Abstract: Thermal treatment applications towards production of energy from raw and pre-treated municipal solid waste (MSW) are continuously growing context in contemporary waste-to-energy technology. The quality of MSW needs an improved analysis to enhance her choice of energy exploitation and environmental assessment of fly and bottom ashes associated with thermochemical conversions. The MSW were collected from municipal solid waste disposal facilities (MSWDF) in Cape Town to investigate heavy metals distributions in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…For Cd, the conversion into filter ash was higher in experiment 3 (lower filter temperature) than that in experiment 4, as expected . Pb conversion to filter ash was also higher than that in bottom ash conversion . Moreover, low-volatile elements, such as Ca, Mg, Na, K, Fe, Al, Si, Ti, and Ba, were expected to be more concentrated in the bottom ash, which was observed in both experiments (3 and 4).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…For Cd, the conversion into filter ash was higher in experiment 3 (lower filter temperature) than that in experiment 4, as expected . Pb conversion to filter ash was also higher than that in bottom ash conversion . Moreover, low-volatile elements, such as Ca, Mg, Na, K, Fe, Al, Si, Ti, and Ba, were expected to be more concentrated in the bottom ash, which was observed in both experiments (3 and 4).…”
Section: Resultssupporting
confidence: 68%
“…50 Pb conversion to filter ash was also higher than that in bottom ash conversion. 51 Moreover, low-volatile elements, such as Ca, Mg, Na, K, Fe, Al, Si, Ti, and Ba, were expected to be more concentrated in the bottom ash, which was observed in both experiments (3 and 4). The concentration of heavy metals in the filter ash fraction may enable different applications for the bottom ash, as long as the composition complies with current legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Higher values observed for the two deeper fractions may come from leaching by rainwater of incombustible particles from the upper to the lower layers of the heap. High ash content in a fuel is undesirable in general, as, among other reasons, it needs to be safely disposed of and may contain significant amounts of heavy metals [12,30]. Compared to the values compiled in [12], which range from 5 to 20%, these results are noticeably higher, which may disqualify the RDF in the presented research from application in certain industries.…”
Section: Discussionmentioning
confidence: 70%
“…The authors, however, wish to note that it is an interesting area of further inquiry. An example of such investigations by other authors can be found, e.g., in [30].…”
Section: Discussionmentioning
confidence: 95%